Integrating Environmental, Social, and Governance Considerations into Company Operations - Benhard, Ronoh (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This manuscript comprehensively analyzes integrating environmental, social, and governance (ESG) considerations into company operations. Through an extensive literature review and case studies of industry leaders like Patagonia, Google, IKEA, Microsoft, and HSBC, the study explores the strategies adopted by corporate managers to align business practices with broader societal and environmental goals. The critique and recommendations address the effectiveness of ESG initiatives, challenges in implementation, cross-functional collaboration, balancing short-term and long-term goals, stakeholder engagement, continuous education, and risk management. The paper concludes by emphasizing the paradigm shift towards responsible and sustainable business practices, with recommendations for ongoing refinement.